Analysis of Visionary Leadership of School Principals to Improve Teacher Performance in Learning: Analisis Kepemimpinan Visioner Kepala Sekolah untuk Meningkatkan Kinerja Guru dalam Pembelajaran - Zuhro, Siti Li’anatuz; Dian, Imelda (Indonesian Journal of Innovation Studies, 2026)
General Background: School leadership plays a strategic role in creating a conducive learning environment and supporting teacher performance. Specific Background: SD Negeri Kepunten has implemented visionary principal leadership through school development, instructional innovation, professional support, and collaborative practices. Knowledge Gap: Previous studies have generally discussed visionary leadership without examining its implementation in a public elementary school facing resource limitations and teacher resistance to innovation. Aims: This study analyzes the characteristics, outcomes, and supporting and inhibiting factors of visionary principal leadership at SD Negeri Kepunten, Tulangan District. Results: Qualitative case study findings show that the principal acts as a direction setter, change agent, future-oriented leader, professional coach, and responsive problem solver, while teachers demonstrate stronger lesson planning, subject mastery, instructional strategies, classroom management, assignment practices, and reflection. Novelty: Responsiveness and solution-oriented action emerge as an additional leadership dimension. Implications: Sustained collaboration, professional development, resource optimization, and responsive leadership are needed. Key Findings Highlights Arah strategis diterjemahkan melalui visi dan misi yang komunikatif serta partisipatif. Pembinaan melalui coaching, supervisi akademik, dan komunitas belajar mendukung praktik pembelajaran yang lebih variatif. Respons cepat dan solutif menjadi karakteristik tambahan dalam menghadapi persoalan sekolah secara kontekstual. Keywords : Visionary Leadership, School Principals, Teacher Performance, Instructional Leadership, Professional Coaching